Association between Age and Trunk Muscle Area and Density in Patients with Spinal Metastases - Sho Dohzono; Ryuichi Sasaoka; Kiyohito Takamatsu; Hiroaki Nakamura (Asian Spine Journal, 2022)
Study Design A retrospective study. Purpose This study aimed to evaluate the relationship between age and trunk muscle composition and between trunk muscle composition and overall survival in patients with spinal metastasis. Overview of Literature A low skeletal muscle mass is associated with a poor overall survival in patients with cancer. However, no previous studies have evaluated the relative effects of age and disease on muscle mass and muscle quality in patients with advanced cancer. Methods This study included 539 patients diagnosed with spinal metastasis from February 2009 to July 2018. The patients were categorized into four groups based on age: <59, 60–69, 70–79, and ≥80 years. Differences in trunk muscle composition among age groups and among groups were classified on the basis of survival (< or >3 months after spinal metastasis diagnosis) were evaluated. Results In total, 515 patients (273 men, 242 women; mean age, 67.8 years) with complete medical records were included in the analysis. No significant differences were observed in the area of the psoas and paravertebral muscles among age groups in either sex. A significant trend toward a low muscle density with the increase in age was found for both sexes. Patients who survived less than 3 months had significantly smaller trunk muscle area than those who survived for more than 3 months in both sexes. Conclusions The results suggest that the reduction in muscle density is associated with advanced age, whereas a decreased muscle area is associated with pathology. Additionally, a small trunk muscle area was associated with a short overall survival. Further studies are needed to elucidate the underlying mechanisms of age- versus cancer-related changes in the muscle area and their influence on overall survival.